2020
DOI: 10.1108/ijshe-05-2020-0186
|View full text |Cite
|
Sign up to set email alerts
|

Open laboratories for social innovation: a strategy for research and innovation in education for peace and sustainable developmentSustainable development is an issue of high relevance for all countries, and universities play a fundamental role in promotin

Abstract: Purpose Sustainable development is an issue of high relevance for all countries and universities play a fundamental role in promoting the participation of society members in achieving this objective. This study aims to conduct an open laboratory of social innovation (OPENLAB_SI) inside a university with society stakeholders, as a research and innovation tool that facilitates addressing the complexity of social problems through the principles of openness, experimentation, inclusion, diversity, participation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…A few studies analyze research activities at the micro-level, tackling single SDGs as well as the overall Agenda 2030. One best practice for universities is to open laboratories of social innovation: optimized spaces where participants (internal and external stakeholders) can collaborate to experiment with ideas, raise concerns, and share best practices (Zermeño and de la Garza, 2020). This stream also outlines other specific actions that can reorient higher education toward sustainable development.…”
Section: Research-micromentioning
confidence: 99%
“…A few studies analyze research activities at the micro-level, tackling single SDGs as well as the overall Agenda 2030. One best practice for universities is to open laboratories of social innovation: optimized spaces where participants (internal and external stakeholders) can collaborate to experiment with ideas, raise concerns, and share best practices (Zermeño and de la Garza, 2020). This stream also outlines other specific actions that can reorient higher education toward sustainable development.…”
Section: Research-micromentioning
confidence: 99%
“…To be more precise, Gómez Zermeño and Alemán de la Garza describes the accumulated experience in conducting an open laboratory of social innovation at the university as a tool that facilitates solving the complexity of social problems through the principles of openness, experimentation, inclusion, diversity, participation and cooperation [17]. This is of high significance in another innovative technology -coaching [3].…”
Section: New Trends and Strategies In The Modern Educational Processmentioning
confidence: 99%
“…[3]. It is also emphasized that "the involvement of social innovations leads to the creation of links between society, academia, the formation of collective knowledge" [17].…”
Section: New Trends and Strategies In The Modern Educational Processmentioning
confidence: 99%
“…One of the few case-studies that exist, Sroufe (2020) acknowledges the potential for student personal skill development in several areas such as teamwork, communication and problem solving, but these skills are not yet measured nor reported on. In a reflection by Gómez Zermeño and Alemán de la Garza (2020) students indicated that their personal skills, namely, problem-solving-, brainstorming- and entrepreneurship skills improved after being engaged in an LL project. This reflection is unfortunately not benchmarked.…”
Section: Introductionmentioning
confidence: 99%
“…In this setting, the campus is the LL and students work on an issue posed by the university with the help of professionals. Another setting is described by Gómez Zermeño and Alemán de la Garza (2020), where universities have laboratories in which students, academia and societal partners collaborate in social innovations quests. This setting is embedded in the concept of co-creation with society by involving citizen participants and is mostly applied to create social innovation.…”
Section: Introductionmentioning
confidence: 99%